2017
DOI: 10.1111/dmcn.13480
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of hip displacement in children with cerebral palsy: a systematic review

Abstract: High-quality evidence on prevention of hip displacement is lacking. No recommendations can be made for preventing hip displacement in children with cerebral palsy because of poor-quality evidence. High-quality, prospective, longitudinal studies investigating the impact of interventions on hip displacement are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 68 publications
1
50
0
3
Order By: Relevance
“…This paper reports purely on the best available evidence, coded using the GRADE framework. We observe that interventions in isolation (including botulinum toxin, intrathecal baclofen, selective dorsal rhizotomy, obturator nerve blocks, positioning, and bracing) have small effect sizes for preventing hip migration [145,147]. In contrast, important clues arise from longitudinal population-based studies in Sweden, which have shown that comprehensive multidisciplinary intervention (including botulinum toxin, weight-bearing, motor training, and orthopedic surgery) at the right time and the right dose can prevent hip dislocation [260].…”
Section: Hip Surveillancementioning
confidence: 98%
“…This paper reports purely on the best available evidence, coded using the GRADE framework. We observe that interventions in isolation (including botulinum toxin, intrathecal baclofen, selective dorsal rhizotomy, obturator nerve blocks, positioning, and bracing) have small effect sizes for preventing hip migration [145,147]. In contrast, important clues arise from longitudinal population-based studies in Sweden, which have shown that comprehensive multidisciplinary intervention (including botulinum toxin, weight-bearing, motor training, and orthopedic surgery) at the right time and the right dose can prevent hip dislocation [260].…”
Section: Hip Surveillancementioning
confidence: 98%
“…Understandably, improvements over a long time period are mixed with natural development and a combination of other treatment modalities. According to a recent systematic review, single or repeated BTXA treatments, either alone or combined with bracing, appeared to decelerate but not to prevent hip displacement [133]. Orthopedic surgery is still important for the prevention and reconstruction of hip dislocation, and to correct and stabilize scoliosis and foot deformities [131].…”
Section: Lessons Learned From the Repeated Treatment Studiesmentioning
confidence: 99%
“…A recent systematic review into interventions that may prevent hip dysplasia in CP did not find SDR to have either a positive or negative effect. 54 When hip surgery is required in a child who is otherwise eligible for SDR, timing of such intervention is discussed later in this review.…”
Section: Outcomes Of Sdrmentioning
confidence: 99%
“…Currently, it is unclear what effect, if any, SDR has on neuromuscular hip dysplasia. 54 However, it is clear that once hip dislocation is established, pain is common and reconstructive options are limited, hence the relative priority this should be given over SDR. Simultaneous SDR and hip reconstruction should be avoided, as one operation will restrict the rehabilitation required by the other.…”
Section: Sdr Within a Multi-disciplinary Multi-modal Approachmentioning
confidence: 99%